Fluconazole-resistant Candida parapsilosis: A new emerging threat in the fungi arena - Escribano, Pilar; Guinea, Jesús (Frontiers in Fungal Biology, 2022)
Candida parapsilosis is a leading cause of invasive candidiasis in southern Europe, Latin America and Asia. C. parapsilosis has been mostly considered susceptible to triazoles, but fluconazole resistance is on the rise in some countries. The main mechanism related to fluconazole resistance is the presence of ERG11p substitutions, dominated by the Y132F amino acid substitution. Isolates harbouring this substitution mimic C. auris given that they may cause hospital outbreaks, become endemic, and emerge simultaneously in distant areas around the world. At the moment, Spain is experiencing a brusque emergence of fluconazole resistance in C. parapsilosis; isolates harbouring the Y132F substitution were detected for the first time in 2019. A recent study on Candida spp isolates from blood cultures collected in 16 hospitals located in the Madrid metropolitan area (2019 to 2021) reported that fluconazole resistance in C. parapsilosis reached as high as 13.6%. Resistance rates rose significantly during those three years: 3.8% in 2019, 5.7% in 2020, and 29.1% in 2021; resistant isolates harboured either the dominant Y132F substitution (a single clone found in four hospitals) or G458S (another clone found in a fifth hospital). The COVID-19 pandemic may have increased the number of candidaemia cases. The reason for such an increase might be a consequence of uncontrolled intra-hospital patient-to-patient transmission in some hospitals, as an increase not only in C. parapsilosis candidaemia episodes but also in the spread of clonal fluconazole-resistant isolates might have occurred in other hospitals during the pandemic period. Patients affected with fluconazole-resistant C. parapsilosis harbouring the Y132F substitution presented a mortality rate ranging from 9% to 78%, were mainly admitted to intensive care wards but did not have differential risk factors compared to those infected by susceptible isolates. With scarce exceptions, few patients (≤20%) infected with fluconazole-resistant isolates had previously received fluconazole, thus supporting the fact that, although fluconazole might have been a key factor to promote resistance, the main driver promoting the spread of fluconazole-resistant isolates was patient-to-patient transmission.